Melawan Radikalisme melalui Website - Rina Sari Kusuma; Nur Azizah (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2018)
Technology always has two faces. Radicalism found its heaven when the Internet can be used as a media for propaganda and for recruiting new members. On the contrary, the Internet could also be used to counter radicalism. Badan Nasional Penanggulangan Terorisme (BNPT) in collaboration with Pusat Media Damai (PMD) has three websites such as jalandamai.org, damailahindonesiaku.com, dan damai.id to support that mission. Using qualitative content analysis, this research aims to describe the way of these websites are fighting online radicalism. This research found that there are two steps that these websites took to propagate anti radicalism, by sensitizing the spread of radicalism and what kind of actual action that can be done to against it.